EVALUASI INTEGRITAS TIANG BOR DENGAN PENGUJIAN CROSSHOLE SONIC LOGGING (CSL) - Dhevi Mulyanda; Rajinda Syadazali Bintan; Siti Nur Indah Sari (PILAR, 2024)
The assesment of structural integrity in civil engineering construction is often assesed for ensuring the safety and the longevity of inftrasturture. A common assesment typically required some attachment sensors on area selection of reviewing before and after construction phase. Bored piles as bottom foundation element that distributed loads from upper structure to the soil layer requires thorough inspection to detect defects from light to heavy damage that may compromise their stability. This study aims to investigate the accuracy and precision of CSL (Crosshole Sonic Logging) as a defect indicator in diagnosing bored pile conditions. The study involves some points of CSL test in the site to identify and quantify potential defects The findings can be used to enhance the understanding of CSL as a diagnostic tool for bored piles and improving the overall foundation assessment methodologies. Keywords : pile assessment, CSL, bored pile, foundation